TOWARDS AVOIDING THE HIDDEN TRAPS IN QFD DURING REQUIREMENTS ESTABLISHMENT - Zhang, Xinwei; Tong, Shurong; Eres, Hakki; Wang, Keqin; Kossmann, Mario (Journal of systems science and systems engineering, 2015)
The Quality Function Deployment （QFD） is a useful and representative methodology to transform customer needs into different level of requirements in a system hierarchy. Simplifications that are based on assumptions are ubiquitous in the QFD, but these underlying assumptions possibly do not hold true, which renders the simplifications unjustified. Additionally, these assumptions are usually not verified within the context of the application domain. This paper identifies and illustrates eight hidden traps in QFD during the process of establishing the requirements, where the assumptions, and therefore, the simplifications made are not reasonable. These traps are implicit in the understanding of customer needs, establishment of system requirements and the flow down of these requirements to lower levels of the system hierarchy. Suggestions are given to help avoiding these hidden traps, thereby eliminating or alleviating their potentially detrimental effects. The intent of the paper is to make readers aware of these traps when applying QFD for the establishment of requirements, so that they may utilize QFD with a better understanding of its limitations and develop higher quality specifications.